Analisis Penyalahgunaan Media Sosial dan Implikasinya Terhadap Prokrastinasi Akademik Siswa SMP Negeri 12 Medan - Anjelly S, Verawati; Angelina Paskah Br Haloho; Naurah Afifah Wida; Naila Aprilia; Virgie Rogabena Sinuraya (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Social media misuse among adolescents has become a significant catalyst for academic issues in the digital era. This study aims to analyze the patterns of social media misuse and its implications for academic procrastination among students of class VIII-5 at SMP Negeri 12 Medan. A descriptive qualitative approach was employed, involving 27 students as subjects. Data were collected through semi-structured interviews and documentation, then analyzed using the Miles and Huberman model (data reduction, display, and conclusion drawing). The findings reveal that 59.3% of students spend 5 to 8 hours daily on platforms such as TikTok, Instagram, and Facebook, primarily for non-academic entertainment. This behavior directly triggers chronic academic procrastination, characterized by the consistent use of the “cramming system” (SKS) for assignments. The study identifies low self-regulation as the primary cause of this phenomenon. Consequently, there is an urgent need for Guidance and Counseling (BK) interventions focused on digital literacy and self-regulated learning to mitigate the negative impact of digital distractions on students’ academic discipline.